Design, synthesis, and in vitro evaluation of cytotoxic analogs of bombesin-like peptides containing doxorubicin or its intensely potent derivative, 2-pyrrolinodoxorubicin - Nagy, Attila (The National Academy of Sciences of the USA, 1997)
Five peptide fragments, based on the C-terminal sequence of bombesin (BN)-(6-14) or BN-(7-14), were selected as carriers for radicals doxorubicin (DOX) and 2-pyrrolino-DOX to create hybrid cytotoxic analogs. All these compounds had a reduced peptide bond (CH(2)-NH or CH(2)-N) between positions 13 (Phe or Leu) and 14 (Phe, Leu, or Tac) (Tac = thiazolidine-4-carboxylic acid). Three pseudononapeptide carriers contained N-terminal d-Phe or d-Tpi at position 6 (Tpi = 2,3,4,9-tetrahydro-1H-pyrido[3,4-b]indole-3-carboxylic acid). Two pseudooctapeptides had Gln(7) at the N terminus. The conjugation of N-(9-fluorenylmethoxycarbonyl)doxorubicin (N-Fmoc-DOX)-14-O-hemiglutarate to the peptide carriers at the N terminus resulted in cytotoxic hybrids of BN-like peptides containing DOX. These hybrids could then be converted to analogs with 2-pyrrolino-DOX by a reaction with 4-iodobutyraldehyde. The ability of the carriers and the conjugates to inhibit the binding of (125)I-labeled [Tyr(4)]BN to receptors for BN/gastrin releasing peptide (GRP) on Swiss 3T3 cells was determined. Cytotoxic conjugates of pseudooctapeptide carrier analogs displayed the highest binding affinity (K(D) ≈1 nM). The cytotoxic BN analogs and their corresponding cytotoxic radicals exerted similar inhibitory effects on the in vitro growth of CFPAC-1 human pancreatic cancer, DMS-53 human lung cancer, PC-3 human prostate cancer, and MKN-45 human gastric cancer cell lines that have receptors for BN/GRP. In DMS-53 cells, the activity of 2-pyrrolino-DOX and its conjugates was ≈2500 times higher than that of DOX and its hybrids. These highly potent cytotoxic analogs of BN have been designed as targeted anti-tumor agents for the treatment of various cancers that possess receptors for BN/GRP.